Descriptive Analysis of Passive Voice Sentence Through Levels Of Semantic Analysis in the Story of A Study In Scarlet By Sir Arthur Conan Doyle - Siti Nurjanah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
Learning English as Foreign Language is not that easy in Indonesia. Mostly learners will face some difficulties in learning it as people speak English as foreign language, and the opportunity to interact with English native speakers is very little. The function of English native teachers is to teach English naturally. Therefore, in this research, the researcher offers one of English grammar features to guide the EFL leaners understand English naturally. In this study, the researcher focusses on the level of semantic analysis which is actually a very basic lesson to learn English. The research methodology used is descriptive qualitative research. The data are passive voice constructions consisting of 42 passive voice sentences from a novel of Sherlock Holmes by the title “A Study in Scarlet”. The data are examined by the researcher herself through a software feature on online application. Afterward, the data are analyzed though levels of semantic analysis. There are three key themes which are analyzed: reference, sense relation and thematic role. In summary, the levels of semantic analysis is successful in analyzing the reference which naturally helps the learners memorize many new words also successful in both knowing the sense relation and thematic role which guide the learners think English word just like first language or second language learners.